Slew rate induced distortion in switched-resistor integrators - Jiraseree-amornkun, A.; Worapishet, A.; Klumperink, E. A.M.; Nauta, B.; Surakampontorn, W. (My University, 2006)
OPAMP-RC integrators built with linear resistors and capacitors can achieve very high linearity. By means of a switched resistor, tuning of the RC time-constant is possible via the duty-cycle of the clock controlling the switched resistor. This paper analyzes the effect of OPAMP slew rate limitations on the distortion of a switched-resistor lossy OPAMP-RC integrator. We show via analysis and simulations that the use of two sets of switched resistors instead of one relaxes the OPAMP slew rate requirements, and reduces the resulting distortion significantly. ©2006 IEEE.